Anaerobic threshold individualized assessment in a young swimmer - Fernandes, R. J.; Sousa, M.; Pinheiro, A.; Vilar, S.; Colaco, P.; Vilas-Boas, J. P. (The Open Sports Sciences Journal, 2010)
The assessment of blood lactate concentrations is considered one essential procedure in physiological diagnosis of swimming performance. Our purpose was to assess the metabolic anaerobic threshold of an 11 year old swimmer through an individualized intermittent incremental protocoomplementarily, stroking parameters were also determined. The subject performed a front crawl 5 x 200 m test, being the velocity controlled by an acoustic signal. The blood samples were collected from the ear lobe at rest and after each step. Stroke rate was registered by a chronofrequencemeter base 3, and stroke length and velocity were calculated at the end of each 200 m. The individual anaerobic threshold occurred at 1.2 mmol/l, rather lower than the traditionally used 4 mmol/l value suggested for trained swimmers. The velocity corresponding to anaerobic threshold was 1.06 m/s, representing a 5 s difference in a 100 m effort comparing to the velocity of 4 mmol/l. Stroke rate increased and stroke length decreased throughout the incremental protocol, i.e., with the velocity increments. It was concluded that the velocity corresponding to 4 mmol/l does not represent the individual anaerobic threshold in this young trained swimmer, and that he prefer to increase their velocity through the raise of stroke rate. Thus, given the importance of developing swimming technique in age-group swimmers, this swimmer should implement the lengthening of his stroke cycles in the training practice routines, trying to resist to the degradation of the stroke length when velocity increases.